2022
DOI: 10.1001/jamahealthforum.2022.0812
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Prevalence and Trajectory of Depressive Symptoms by Sexual Orientation During Physician Training

Abstract: This cohort study uses survey data to assess the prevalence and development of depressive symptoms among sexual minority and heterosexual physicians during residency training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Emerging evidence indicates that sexual minority (ie, bisexual or homosexual) individuals in medical training experience higher levels of depression than their heterosexual counterparts . Previous studies involving IHS participants reported that sexual minority individuals enter residency with higher PHQ-9 scores than their heterosexual peers and experience a more pronounced increase in depressive symptoms throughout their internship . As inclusivity in our profession increases, there is an ongoing need to support this diverse workforce appropriately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence indicates that sexual minority (ie, bisexual or homosexual) individuals in medical training experience higher levels of depression than their heterosexual counterparts . Previous studies involving IHS participants reported that sexual minority individuals enter residency with higher PHQ-9 scores than their heterosexual peers and experience a more pronounced increase in depressive symptoms throughout their internship . As inclusivity in our profession increases, there is an ongoing need to support this diverse workforce appropriately.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Previous studies involving IHS participants reported that sexual minority individuals enter residency with higher PHQ-9 scores than their heterosexual peers and experience a more pronounced increase in depressive symptoms throughout their internship. 26 As inclusivity in our profession increases, there is an ongoing need to support this diverse workforce appropriately.…”
Section: Discussionmentioning
confidence: 99%